(untitled) (Sebha University Conference Proceedings, 2024)
The Study Aims At Knowing The Nutritional Culture In The Physical State Of Secondary School Students, For This Reason We Follow The descriptive Method By Scanning TO Suit The study Where The Sample Population Is 160 From The Third Year Secondary School Is Distributed In ten Secondary School In Tlemcen City, Which Is Chosen In an International Way That Faithfully Represented The Statistical Population, TO Collect Data We Use Nutritional Cultural Scale And Physical Scale; The Most Important Result Of The Study Show That There Is An Average Level In Both Nutritional Culture And Physical State For Final Year Students In Secondary Education, In Addition To A Correlation Between Nutritional Culture And Physical State For Third Year Secondary Students There is also a relationship between nutritional culture and physical condition among students in the second year of secondary school, as food has an important role in increasing muscle strength and muscular endurance. Familiarity with nutritional culture and commitment to healthy eating habits are among the factors that help raise the level of physical efficiency and increase speed. Hospitalization.